Peningkatan Kompetensi Guru dalam Mengembangkan RPP 1 Lembar Melalui Supervisi Akademik Kelompok Teknik Workshop di MTs Negeri 3 Bantul - Muhari, Sugeng (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to determine the improvement of teacher competence in developing a 1-sheet Learning Implementation Plan (RPP) through academic supervision of workshop techniques. This study used school action research with two cycles. The subjects of the study were subject teachers at MTs Negeri 3 Bantul, totalling 28 people. Research instruments in the form of workshop assessment sheets and 1-sheet RPP supervision / assessment sheets. The results showed that in cycle I an average score of 74 was obtained in the good category, increasing quite significantly in cycle II with an average value of 90 in the very good category. The application of academic supervision of workshop techniques can improve the competence of subject teachers in developing RPP 1 sheet. This research has special implications for madrasah heads and madrasah supervisors to implement academic supervision of workshop techniques so that teacher competence can further develop.